2015
DOI: 10.1021/acs.iecr.5b01342
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Pelleting, and Performance Evaluation of a Novel K-Promoted γ-Alumina/MgAl-Layered Double Oxide Composite Adsorbent for Warm Gas H2/CO2 Separation

Abstract: Development of stable solid adsorbent in pellet form is of importance for CO 2 /H 2 separation at elevated temperature (250−450°C). This study provides a novel synthesis method by adding K 2 CO 3 solution into alumina sol soaked MgAl-layered double hydroxide paste. The delay time of K 2 CO 3 addition is studied to demonstrate that the formation of Kpromoted γ-alumina is facilitated by an immediate addition. Extruded adsorbent of higher CO 2 capacity (0.65 mmol/g) and radial crushing strength (75.6 N per pellet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Up until now, the research on MgAl-CO 3 LDHs and MgAl-CO 3 LDHs-derived mixed oxides mainly concentrates on developing novel preparation methods, , replacing the intercalation inorganic or organic anions, , changing the molar ratio of Mg/Al, employing the supporters, doping alkali metal (K, Na, Cs), and exploring sorption/desorption kinetics . Among diversified preparation methods, the coprecipitation method is the most common one.…”
Section: Introductionmentioning
confidence: 99%
“…Up until now, the research on MgAl-CO 3 LDHs and MgAl-CO 3 LDHs-derived mixed oxides mainly concentrates on developing novel preparation methods, , replacing the intercalation inorganic or organic anions, , changing the molar ratio of Mg/Al, employing the supporters, doping alkali metal (K, Na, Cs), and exploring sorption/desorption kinetics . Among diversified preparation methods, the coprecipitation method is the most common one.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from improving the CO 2 capture capacity and cycling stability, overcoming the particle size issue is a very important aspect on the development of CO 2 capture sorbents. There are efforts to address these issues in other high temperature sorbents such as CaO and Li 4 SiO 4 by developing structured forms of the materials. However, these issues have been largely ignored for LDH-based MMOs sorbents. , …”
Section: Introductionmentioning
confidence: 99%
“…The progress on dramatically enhanced adsorption selectivity and capacity of TiO 2 adsorbents by RADS unlocks its potential for ultradeep desulfurization of fuels, which is, however, still limited to powdered adsorbents. Due to the challenges of high-pressure drop of powdered adsorbents in the packed bed, as well as material losses in multiple cycles, molding TiO 2 -based ADS adsorbents into customizable forms and their regeneration are considered as essential steps and cannot be underestimated when considering potential industrial applications. , Most recent research studies have focused on the adsorption performance and mechanism of desulfurization. However, studies on the adsorption kinetics and regeneration of molded materials are rarely reported. As indispensable parts of the RADS process, the adsorption kinetics of materials affect the desulfurization rate and the regeneration performance of adsorbents, which subsequently influence the adsorbent durability for industrial applications .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the challenges of highpressure drop of powdered adsorbents in the packed bed, as well as material losses in multiple cycles, molding TiO 2 -based ADS adsorbents into customizable forms and their regeneration are considered as essential steps and cannot be underestimated when considering potential industrial applications. 31,32 Most recent research studies have focused on the adsorption performance and mechanism of desulfurization. 33−35 However, studies on the adsorption kinetics and regeneration of molded materials are rarely reported.…”
Section: Introductionmentioning
confidence: 99%